2018
DOI: 10.1111/dom.13417
|View full text |Cite
|
Sign up to set email alerts
|

New clinical trial designs for establishing drug efficacy and safety in a precision medicine era

Abstract: Despite advances in pharmacotherapy, diabetic kidney disease (DKD) remains associated with a high burden of micro‐ and macrovascular complications often leading to premature mortality. New therapies are highly desirable to mitigate the burden of this disease. However, there are a number of barriers that hamper drug development in DKD. These include, amongst others, the lengthy and complex clinical trials required to prove drug efficacy and safety, inefficiencies in clinical trial conduct, and the high costs as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 22 publications
0
35
0
Order By: Relevance
“…Individual characteristics may influence the magnitude of the treatment response to liraglutide . We showed that a high baseline level of HbA1c, SBP and LDL‐cholesterol was associated with a greater response in the corresponding variable.…”
Section: Discussionmentioning
confidence: 83%
“…Individual characteristics may influence the magnitude of the treatment response to liraglutide . We showed that a high baseline level of HbA1c, SBP and LDL‐cholesterol was associated with a greater response in the corresponding variable.…”
Section: Discussionmentioning
confidence: 83%
“…In addition to these efforts, advanced clinical trial designs may help with translation for precision medicine. Different trial types, such as umbrella, basket or platform trials, can offer the framework needed for segmentation of patients during clinical trials, as well as methods to test multiple therapies in parallel to decrease costs …”
Section: Future Prospects In 3d Printing For Precision Medicinementioning
confidence: 99%
“…Different trial types, such as umbrella, basket or platform trials, can offer the framework needed for segmentation of patients during clinical trials, as well as methods to test multiple therapies in parallel to decrease costs. [134] www.advmat.de www.advancedsciencenews.com…”
Section: Future Prospects In 3d Printing For Precision Medicinementioning
confidence: 99%
“…There is a caveat though, that is that these enrichment designs may be non‐informative on the biomarker‐negative population . As described elsewhere in this issue of the Journal, platform, basket and umbrella trials may offer additional innovative study designs for evidence generation in the setting of precision‐medicine . In addition, observational “real‐world” data may be increasingly considered to provide further evidence postapproval .…”
Section: New Clinical Trial Designs For Precision Medicine In Regulatmentioning
confidence: 99%